Study on seismic performance of high-strength steel earthquake-resilient beam-column joint with double damage elements - Hongchao Guo; Dongdong Zheng; Jing Lu; Xudong Zhou; Wenqi Wang; Yunhe Liu (Sustainable Structures)
The mutual constraint between bearing capacity, stiffness, and post earthquake recoverability has always been the contradiction of earthquake resilient joint. Taking into account the above three factors, this paper proposes a high-strength steel earthquake resilient beam column joint with double damage elements. Low cycle reciprocating loading tests were conducted, and a refined finite element model was established for parameter expansion analysis. The research findings show a significant time sequence in the joint double damage element, with both components dissipating over 90% of energy. In contrast, main components like beams and columns dissipate less than 10% of energy. The residual deformation of the joints is within the specified DS2 level limit in the FEAM P-58 standard, indicating excellent post-earthquake recoverable performance. The influence of the length lb of the energy dissipation section in the middle of the flange cover plate, the height hs of the stiffening rib, the length lc of the cantilever beam, and the cutting angle αa of the butterfly damper on the joint performance was studied. The results show that lb significantly affects the loading stability of the flange cover plate, thereby affecting the joint performance. It is recommended to ensure that the stability coefficient of the flange cover plate is not less than 0.967; Considering all factors, it is recommended that hs be taken as 0.2 times the width of the flange cover plate, lc be taken as 1.3 times the height of the beam, and αa taken as 50°. Finally, a calculation method for the joint trilinear skeleton curve model was proposed through theoretical derivation and data fitting. By comparing the theoretical calculation results with experimental and finite element calculation results, it was found that the curves matched well, proving the effectiveness of the proposed joint skeleton curve calculation method.